Preparation and properties of nylon 6/sulfonated graphene composites by an in situ polymerization process. Issue 51 (9th May 2016) - Wang, Chunhua; Hu, Feng; Yang, Kejian; Hu, Tianhui; Wang, Wenzhi; Deng, Rusheng; Jiang, Qibin; Zhang, Hailiang
Abstract : Nylon 6/sulfonated graphene composites with high thermal conductivity, good mechanical properties and excellent processability were prepared using sulfonated graphene as a precursor by an in situ polymerization process. Abstract : Nylon 6/sulfonated graphene (NSG) composites were prepared using sulfonated graphene (SG) with strong polar sulfonic acid groups as a precursor by the in situ hydrolytic ring-opening polymerization of ε-caprolactam. SG dissolved in the water and then quickly dispersed in an ε-caprolactam melt with simple stirring in an autoclave. The generated PA6 chains were covalently grafted onto SG sheets by the condensation reaction between the active amino groups at PA6 chain terminals and the sulfonic acid groups on SG sheets. The grafted structure and SG content have a great effect on their properties. Compared with pure nylon 6 (PA6), the mechanical properties of NSG composites can be maintained and even enhanced by the use of an appropriate SG content. Research on crystallization and rheological behaviors indicate that NSG composites have a faster crystallization rate and higher flowability than pure PA6, which are beneficial for the use of rapid molding processes. Moreover, the homogeneous dispersion of SG sheets in NSG composites is conducive to the formation of consecutive thermal conductive paths or networks at a relatively low SG content, which significantly improves the thermal conductivity from 0.203 W m −1 K −1 for pure PA6 to 0.398 W m −1 K −1 for a NSG composite with only 3 wt% SG content. Such NSG composites with a simple preparation process, good mechanical properties, excellent processability and high thermal conductivity provide great promise for wider applications of PA6 materials in thermal conductive systems.